142k views
3 votes
Solve

y^2 + 3y = -1



-PlushDNA

1 Answer

5 votes

Answer:


y=-(3+√(5))/(2) AND
y=-(3-√(5))/(2)

Explanation:

Given:
y^2+3y=-1

To solve for
y, we need to get everything on one side of the equal sign and set it to zero. We can do this by adding 1 to both sides. We then get:


y^2+3y+1=0

We can solve for
y by using the quadratic formula:


y=(-b+√((b)^2-4(a)(c)))/(2a) AND
y=(-b-√((b)^2-4(a)(c)))/(2a)

Let's identify our values:


a: 1\\b: 3\\c: 1

Plug in the values and simplify.


y=(-3+√((3)^2-4(1)(1)))/(2(1))\\y=(-3+√(5))/(2)\\-------------------------\\y=(-3-√((3)^2-4(1)(1)))/(2(1))\\\\y=(-3-√(5))/(2)\\

Your final answers are:


y=-(3+√(5))/(2) AND
y=-(3-√(5))/(2)

User Tim Wickstrom
by
4.1k points